A companion to the anthropology of education - Levinson, Bradley A.; Pollock, Mica (Blackwell companions to anthropology ;, 2011)
"A Companion to the Anthropology of Education presents a comprehensive and state-of-the-art overview of the field, exploring the social and cultural dimension of educational processes in both formal and nonformal settings. Explores theoretical and applied approaches to cultural practice in a diverse range of educational settings around the world, in both formal and non-formal contexts Includes contributions by leading educational anthropologists Integrates work from and on many different national systems of scholarship, including China, the United States, Africa, the Middle East, Colombia, Mexico, India, the United Kingdom, and Denmark Examines the consequences of history, cultural diversity, language policies, governmental mandates, inequality, and literacy for everyday educational processes "--